Atuação do enfermeiro na prevenção do choque hipovolêmico - Rodrigues, Maria Socorro Pereira (1981)
The purpose of the study was to verify if the nurse, treating the patient admitted to the hospital, is adopting nieasures that are preventive and eficacious to v.ard the dctectlon of hipovolemic crises in their early stages, and to intercept their course before some grave complications could occur. The population included in the experience consisted of 75 percent of the nurses assigned to the medicai - surgical units of slx general hospitais in Fortaleza, Ceará , The result indicated that despite some basic factors that intcrfer, the nurses to whom was applicd the test, are attentive to wliat occurs, and are a dopting strategies of action that make possible to detect and / or foresee episodes of hipovolemic shoclí in the early stages .